2020
DOI: 10.3390/app10051618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Conifer Wood Biochar as Growing Media Component for Citrus Nursery

Abstract: (1) Background: The commercial sustainability of the citrus nursery industry involves cutting costs by using alternative planting substrates to replace (or partially replace) the conventional black peat. Conifer wood biochar was evaluated as a component of the growth medium in a commercial citrus nursery for Carrizo citrange seedlings. (2) Methods: Seven growth media mixtures (A–G) were tested. Each mixture consisted of 50% sandy volcanic soil with the remaining 50% made up as follows: A = black peat and perli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Hence, there is a continuous search for sustainable growing media substitutes, such as biochar (Figure 5). Ferlito et al (2020) evaluated conifer wood BC as a growing medium component for citrus nurseries. The authors found that BC (25%) could be used in growing media comprising 50% sandy volcanic soil and 25% black peat or combined with compost (1:1) for healthy citrus production.…”
Section: Biochar As a Component Of Container Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, there is a continuous search for sustainable growing media substitutes, such as biochar (Figure 5). Ferlito et al (2020) evaluated conifer wood BC as a growing medium component for citrus nurseries. The authors found that BC (25%) could be used in growing media comprising 50% sandy volcanic soil and 25% black peat or combined with compost (1:1) for healthy citrus production.…”
Section: Biochar As a Component Of Container Substratesmentioning
confidence: 99%
“…Hence, there is a continuous search for sustainable growing media substitutes, such as biochar ( Figure 5 ). Ferlito et al. (2020) evaluated conifer wood BC as a growing medium component for citrus nurseries.…”
Section: Biochar Application Sequestrates Greenhouse Gases Improves S...mentioning
confidence: 99%
“…Regarding physical characteristics, the quantity and distribution of sand, clay, and silt was obtained by particle-size analysis using the "micro-pipette" method [64]. In terms of chemical properties, total nitrogen (N), organic matter (OM), soil extractable phosphorus (mg/kg), soil exchangeable potassium (meq/100 g), cation exchange capacity, pH, and electrical conductivity (EC) determinations were determined as described in [65][66][67][68][69][70][71]. Total nitrogen was measured by Kjeldahl digestion using a Buchi Labortechnik GmbH N analyzer, and organic matter (OM) was measured by quantifying total organic carbon (TOC, mg•kg −1 ).…”
Section: Soil Analysis and Climatic Datamentioning
confidence: 99%
“…In terms of physical biochar properties, the biochar particle size distribution affects structural properties (i.e., bulk density, water holding capacity and porosity etc.) and nutrient availability in the medium (Ferlito et al 2020;Prasad et al 2020). All these physical properties of the growing medium are heavily dependent on the production conditions (i.e.…”
Section: )mentioning
confidence: 99%
“…For tomato, BC75P25 and BC50P50 treatments had highest shoot lengths in germinated seeds compared to P100 (240% and 258% increase in BC75P25 and BC50P50 respectively). Root length is a key indicator for the initial establishment phase of seedlings in growing media (Landis et al 2009;Ferlito et al 2020).…”
Section: Seed Germinationmentioning
confidence: 99%